Efficient Energy Management in Wireless Sensor Networks Using Edge Sensor Node-Based Routing Protocols - Dhari Ali Mahmood; Yahiea Al Naiemy (Diyala Journal of Engineering Sciences)
Wireless Sensor Networks (WSNs) provide infrastructure for Various environments and appli- cations that require these sensors must operate in, leading to many challenges, including energy. An Energy-Efficient Edge Routing Protocol (EEERP) has been presented in this paper, the proposed protocol addresses the critical challenge of energy efficiency by leveraging edge sensor nodes(ESNs) strategically positioned at the borders of clusters to act as gateways. The proposed protocol increases the efficiency of whole network by introduce ESNs that facilitate efficient data transmission between sensor nodes and the Base Station(BS). The process of node selection take into consideration in EEERP, where the node with low energy level automatically assigned new ESN, to ensuring continuous network operation and optimal performance. Analysis of the EEERP results validate through MATLAB simulation to compareing it against established protocols such as the performance efficient data aggregation protocol(PEDAP) and high quality of service routing algorithm(HQRA). The results show that EEERP significantly enhances energy efficiency, network stability, and overall operational lifespan. The reliability of the WSN increases as demonstrated in results based dynamic clustering with gateways at cluster border-based ESNs.